module Data.Fin.Closure where
private variable
: Level
ℓ : Type ℓ
A B C : Nat k l m n
Closure of finite sets🔗
In this module, we prove that the finite sets are closed under “typal arithmetic”: The initial and terminal objects are finite (they have 1 and 0 elements respectively), products of finite sets are finite, coproducts of finite sets are finite, and functions between finite sets are finite. Moreover, these operations all correspond to arithmetic operations on the natural number indices: etc.
Zero, one, successors🔗
The finite set is an initial object, and the finite set is a terminal object:
: Fin 0 ≃ ⊥
Finite-zero-is-initial .fst ()
Finite-zero-is-initial .snd .is-eqv ()
Finite-zero-is-initial
: is-contr (Fin 1)
Finite-one-is-contr .centre = fzero
Finite-one-is-contr .paths i with fin-view i
Finite-one-is-contr ... | zero = refl
The successor operation on indices corresponds to taking coproducts with the unit set.
: Fin (suc n) ≃ (⊤ ⊎ Fin n)
Finite-successor {n} = Fin-suc ∙e Maybe-is-sum Finite-successor
Addition🔗
For binary coproducts, we prove the correspondence with addition in steps, to make the proof clearer:
module _ where private
: (Fin n ⊎ Fin m) ≃ Fin (n + m)
Finite-coproduct {zero} {m} =
Finite-coproduct (Fin 0 ⊎ Fin m) ≃⟨ ⊎-apl Finite-zero-is-initial ⟩
(⊥ ⊎ Fin m) ≃⟨ ⊎-zerol ⟩
Fin m ≃∎{suc n} {m} =
Finite-coproduct (Fin (suc n) ⊎ Fin m) ≃⟨ ⊎-apl Finite-successor ⟩
((⊤ ⊎ Fin n) ⊎ Fin m) ≃⟨ ⊎-assoc ⟩
(⊤ ⊎ (Fin n ⊎ Fin m)) ≃⟨ ⊎-apr (Finite-coproduct {n} {m}) ⟩
(⊤ ⊎ Fin (n + m)) ≃⟨ Finite-successor e⁻¹ ⟩
(suc (n + m)) ≃∎ Fin
: ∀ {m n} → (Fin m ⊎ Fin n) ≃ Fin (m + n)
Finite-coproduct {m} {n} = Iso→Equiv (to , iso from ir il) where
Finite-coproduct to : Fin m ⊎ Fin n → Fin (m + n)
to (inl x) = record
{ lower = x .lower
; bounded = forget (≤-trans (to-ℕ< x .snd) (+-≤l m n))
}
to (inr (fin i ⦃ forget α ⦄)) =
let
.p : m + i Nat.< m + n
= ≤-trans (≤-refl' (sym (+-sucr m i))) (+-preserves-≤ m m (suc _) n ≤-refl α)
p in record
{ lower = m + i
; bounded = forget p
}
: Fin (m + n) → Fin m ⊎ Fin n
from (fin i ⦃ forget b ⦄) with holds? (i Nat.< m)
from ... | yes p = inl (fin i ⦃ forget p ⦄)
... | no ¬p =
let
: m Nat.≤ i
p' = ≤-peel (<-from-not-≤ _ _ ¬p)
p'
: i - m Nat.≤ i
q = monus-≤ i m
q
.r : i - m Nat.< n
= +-reflects-≤l (suc (i - m)) n m (≤-trans (≤-refl' (+-sucr m (i - m))) (≤-trans (≤-refl' (ap suc (monus-inversel i m p'))) b))
r in inr (fin (i - m) ⦃ forget r ⦄)
: is-right-inverse from to
ir (fin i ⦃ forget b ⦄) with holds? (i Nat.< m)
ir ... | yes p = fin-ap refl
... | no ¬p = fin-ap (monus-inversel i m (≤-peel (<-from-not-≤ _ _ ¬p)))
: is-left-inverse from to
il (inl (fin i ⦃ forget b ⦄)) with holds? (i Nat.< m)
il ... | yes p = refl
... | no ¬p = absurd (¬p b)
(inr (fin i ⦃ forget b ⦄)) with holds? ((m + i) Nat.< m)
il ... | yes p = absurd (¬sucx≤x m (+-reflects-≤l (suc m) m i (≤-trans (≤-refl' (+-sucr i m ∙ ap suc (+-commutative i m))) (≤-trans p (+-≤r i m)))))
... | no ¬p = ap inr (fin-ap (monus-inverser i m))
Sums🔗
We also have a correspondence between “coproducts” and “addition” in
the iterated case: If you have a family of finite types (represented by
a map to their cardinalities), the dependent sum of that family
is equivalent to the iterated binary sum
of the cardinalities:
: ∀ n → (Fin n → Nat) → Nat
sum = zero
sum zero f (suc n) f = f fzero + sum n (f ∘ fsuc)
sum
: (B : Fin n → Nat) → Σ (Fin _) (Fin ∘ B) ≃ Fin (sum n B)
Finite-sum {zero} B .fst ()
Finite-sum {zero} B .snd .is-eqv ()
Finite-sum {suc n} B =
Finite-sum (Fin (suc n)) (Fin ∘ B) ≃⟨ Fin-suc-Σ ⟩
Σ (B 0) ⊎ Σ (Fin n) (Fin ∘ B ∘ fsuc) ≃⟨ ⊎-apr (Finite-sum (B ∘ fsuc)) ⟩
Fin (B 0) ⊎ Fin (sum n (B ∘ fsuc)) ≃⟨ Finite-coproduct ⟩
Fin (sum (suc n) B) ≃∎ Fin
Multiplication🔗
Recall (from middle school) that the product is the same thing as summing together copies of the number Correspondingly, we can use the theorem above for general sums to establish the case of binary products:
module _ where private
: (Fin n × Fin m) ≃ Fin (n * m)
Finite-multiply {n} {m} =
Finite-multiply (Fin n × Fin m) ≃⟨ Finite-sum (λ _ → m) ⟩
(sum n (λ _ → m)) ≃⟨ path→equiv (ap Fin (sum≡* n m)) ⟩
Fin (n * m) ≃∎
Fin where
: ∀ n m → sum n (λ _ → m) ≡ n * m
sum≡* = refl
sum≡* zero m (suc n) m = ap (m +_) (sum≡* n m) sum≡*
: ∀ {m n} → (Fin m × Fin n) ≃ Fin (m * n)
Finite-multiply {zero} {n} = fst , record { is-eqv = λ o → absurd (Fin-absurd o) }
Finite-multiply {suc n} {zero} = ((λ (_ , x) → absurd (Fin-absurd x))) , record { is-eqv = λ o → absurd (Fin-absurd (subst Fin (*-zeror n) o)) }
Finite-multiply {m@(suc m')} {n@(suc n')} = Iso→Equiv (to , iso from ir il) where
Finite-multiply to : Fin m × Fin n → Fin (m * n)
to (fin i ⦃ forget b ⦄ , fin j ⦃ forget b' ⦄) = fin (i * n + j) ⦃ forget α ⦄ where
: i * n + j Nat.< m * n
α =
α let
: i * n + j Nat.≤ m' * n + n'
it = +-preserves-≤ (i * n) (m' * n) j n' (*-preserves-≤r i m' n (≤-peel (recover b))) (≤-peel (recover b'))
it in s≤s (≤-trans it (≤-refl' (+-commutative (m' * n) n')))
: Fin (m * n) → Fin m × Fin n
from (fin i ⦃ forget b ⦄) with divmod q r quot rem ← divide-pos i n =
from let
.b' : q Nat.≤ m
= *-cancel-≤r n {q} {m} $
b' (difference→≤ r (sym quot)) (≤-sucr (≤-peel b))
≤-trans
.ne : q ≠ m
=
ne p let
: m * n Nat.≤ i
p' = difference→≤ r (sym (subst (λ e → i ≡ e * suc n' + r) p quot))
p' in ¬sucx≤x _ (≤-trans b p')
in fin q ⦃ forget (<-from-≤ ne b') ⦄ , fin r ⦃ forget rem ⦄
: is-right-inverse from to
ir (fin i ⦃ forget b ⦄) = fin-ap (sym (is-divmod i n))
ir
: is-left-inverse from to
il (fin i ⦃ forget b ⦄ , fin j ⦃ forget b' ⦄) =
il let
: Path (DivMod (i * n + j) n) (divide-pos (i * n + j) n) (divmod i j refl b')
p = prop!
p in fin-ap (ap DivMod.quot p) ,ₚ fin-ap (ap DivMod.rem p)
Products🔗
Similarly to the case for sums, the cardinality of a dependent
product of finite sets is the product
of the cardinalities:
: ∀ n → (Fin n → Nat) → Nat
product = 1
product zero f (suc n) f = f fzero * product n (f ∘ fsuc)
product
: (B : Fin n → Nat) → (∀ x → Fin (B x)) ≃ Fin (product n B)
Finite-product {zero} B .fst _ = fzero
Finite-product {zero} B .snd = is-iso→is-equiv λ where
Finite-product .is-iso.inv _ ()
.is-iso.linv _ → funext λ ()
.is-iso.rinv fzero → refl
.is-iso.rinv (fin (suc i) ⦃ forget p ⦄) → absurd (¬suc≤0 (≤-peel p))
{suc n} B =
Finite-product (∀ x → Fin (B x)) ≃⟨ Fin-suc-Π ⟩
(B fzero) × (∀ x → Fin (B (fsuc x))) ≃⟨ Σ-ap-snd (λ _ → Finite-product (B ∘ fsuc)) ⟩
Fin (B fzero) × Fin (product n (B ∘ fsuc)) ≃⟨ Finite-multiply ⟩
Fin (B fzero * product n (B ∘ fsuc)) ≃∎ Fin
Permutations🔗
We show that the set of permutations
is finite with cardinality
(the factorial
of
We start by showing that a permutation of is determined by what happens to and by the remaining permutation of
Fin-permutations-suc: ∀ n → (Fin (suc n) ≃ Fin (suc n)) ≃ (Fin (suc n) × (Fin n ≃ Fin n))
= to , is-iso→is-equiv is where
Fin-permutations-suc n to : (Fin (suc n) ≃ Fin (suc n)) → Fin (suc n) × (Fin n ≃ Fin n)
to e .fst = e · 0
to e .snd .fst i = avoid (e · 0) (e · fsuc i) λ p →
(ap lower (Equiv.injective e p))
zero≠suc to e .snd .snd = Fin-injection→equiv _ λ p →
(Equiv.injective e (avoid-injective (e · 0) p))
fsuc-inj
: is-iso to
is .is-iso.inv (n , e) = record { fst = fun ; snd = Fin-injection→equiv _ inj } module inv where
is : Fin (suc _) → Fin (suc _)
fun with fin-view i
fun i ... | zero = n
... | suc x = skip n (e · x)
: injective fun
inj {i} {j} p with fin-view i | fin-view j
inj ... | zero | zero = refl
... | zero | suc y = absurd (skip-skips n _ (sym p))
... | suc i | zero = absurd (skip-skips n _ p)
... | suc i | suc j = ap fsuc (Equiv.injective e (skip-injective n _ _ p))
.is-iso.rinv (n , e) = Σ-pathp refl (ext λ i → avoid-skip n (e · i))
is .is-iso.linv e = ext p where
is : ∀ x → inv.fun (e · 0) (to e .snd) x ≡ e · x
p with fin-view x
p x ... | zero = refl
... | suc i = skip-avoid (e · 0) (e · fsuc i)
We can now show that by induction.
: ∀ n → (Fin n ≃ Fin n) ≃ Fin (factorial n)
Fin-permutations = is-contr→≃
Fin-permutations zero (contr id≃ λ _ → ext λ ()) Finite-one-is-contr
(suc n) =
Fin-permutations (suc n) ≃ Fin (suc n) ≃⟨ Fin-permutations-suc n ⟩
Fin (suc n) × (Fin n ≃ Fin n) ≃⟨ Σ-ap-snd (λ _ → Fin-permutations n) ⟩
Fin (suc n) × Fin (factorial n) ≃⟨ Finite-multiply ⟩
Fin (factorial (suc n)) ≃∎ Fin
Decidable subsets🔗
Given a decidable predicate on we can compute such that is equivalent to the subset of on which the predicate holds: a decidable proposition is finite (it has either or elements), so we can reuse our proof that finite sums of finite types are finite.
Dec→Fin: ∀ {ℓ} {A : Type ℓ} → is-prop A → Dec A
→ Σ Nat λ n → Fin n ≃ A
(no ¬a) .fst = 0
Dec→Fin ap (no ¬a) .snd =
Dec→Fin ap (Finite-zero-is-initial .fst) ¬a
is-empty→≃ (yes a) .fst = 1
Dec→Fin ap (yes a) .snd =
Dec→Fin ap (is-prop∙→is-contr ap a)
is-contr→≃ Finite-one-is-contr
Finite-subset: ∀ {n} (P : Fin n → Type ℓ)
→ ⦃ ∀ {x} → H-Level (P x) 1 ⦄
→ ⦃ dec : ∀ {x} → Dec (P x) ⦄
→ Σ Nat λ s → Fin s ≃ Σ (Fin n) P
{n = n} P ⦃ dec = dec ⦄ =
Finite-subset
sum n ns , Finite-sum ns e⁻¹ ∙e Σ-ap-snd eswhere
: Fin n → Nat
ns = Dec→Fin (hlevel 1) dec .fst
ns i : (i : Fin n) → Fin (ns i) ≃ P i
es = Dec→Fin (hlevel 1) dec .snd es i
Decidable quotients🔗
As a first step towards coequalisers, we show that the quotient of a finite set by a decidable congruence is finite.
Finite-quotient: ∀ {n ℓ} (R : Congruence (Fin n) ℓ) (open Congruence R)
→ ⦃ _ : ∀ {x y} → Dec (x ∼ y) ⦄
→ Σ Nat λ q → Fin q ≃ Fin n / _∼_
This amounts to counting the number of equivalence classes of We proceed by induction on the base case is trivial.
{zero} R .fst = 0
Finite-quotient {zero} R .snd .fst ()
Finite-quotient {zero} R .snd .snd .is-eqv = elim! λ () Finite-quotient
For the induction step, we restrict along the successor map to get a congruence on whose quotient is finite.
{suc n} {ℓ} R = go where
Finite-quotient module R = Congruence R
: Congruence (Fin n) ℓ
R₁ = Congruence-pullback fsuc R
R₁ module R₁ = Congruence R₁
: Σ Nat λ q → Fin q ≃ Fin n / R₁._∼_
n/R₁ = Finite-quotient {n} R₁ n/R₁
In order to compute the size of the quotient we decide whether is related by to any using the omniscience of finite sets.
go: ⦃ Dec (Σ (Fin n) (λ i → fzero R.∼ fsuc i)) ⦄
→ Σ Nat (λ q → Fin q ≃ Fin (suc n) / R._∼_)
If so, lives in the same equivalence class as and the size of the quotient remains unchanged.
(i , r) ⦄ .fst = n/R₁ .fst
go ⦃ yes (i , r) ⦄ .snd = n/R₁ .snd ∙e Iso→Equiv is where
go ⦃ yes : Iso (Fin n / R₁._∼_) (Fin (suc n) / R._∼_)
is .fst = Coeq-rec (λ x → inc (fsuc x)) λ (x , y , s) → quot s
is .snd .inv = Coeq-rec fn λ (i , j , s) → resp i j s where
is : Fin (suc n) → Fin n / R₁._∼_
fn with fin-view j
fn j ... | zero = inc i
... | suc x = inc x
: ∀ i j → i R.∼ j → fn i ≡ fn j
resp with fin-view i | fin-view j
resp i j s ... | zero | zero = refl
... | zero | suc y = quot (R.symᶜ r R.∙ᶜ s)
... | suc x | zero = quot (s R.∙ᶜ r)
... | suc x | suc y = quot s
.snd .rinv = elim! (Fin-cases (quot (R.symᶜ r)) (λ _ → refl))
is .snd .linv = elim! λ _ → refl is
Otherwise, creates a new equivalence class for itself.
.fst = suc (n/R₁ .fst)
go ⦃ no ¬r ⦄ .snd = Finite-successor ∙e ⊎-apr (n/R₁ .snd) ∙e Iso→Equiv is where
go ⦃ no ¬r ⦄ to : Fin (suc n) → ⊤ ⊎ (Fin n / R₁._∼_)
to i with fin-view i
... | zero = inl _
... | suc x = inr (inc x)
: ∀ i j → i R.∼ j → to i ≡ to j
resp with fin-view i | fin-view j
resp i j s ... | zero | zero = refl
... | zero | suc y = absurd (¬r (y , s))
... | suc x | zero = absurd (¬r (x , R.symᶜ s))
... | suc x | suc y = ap inr (quot s)
: Iso (⊤ ⊎ (Fin n / R₁._∼_)) (Fin (suc n) / R._∼_)
is .fst (inl tt) = inc 0
is .fst (inr x) = Coeq-rec (λ x → inc (fsuc x)) (λ (x , y , s) → quot s) x
is .snd .inv = Coeq-rec to λ (x , y , r) → resp x y r
is .snd .rinv = elim! (Fin-cases refl (λ _ → refl))
is .snd .linv (inl tt) = refl
is .snd .linv (inr x) = elim x where
is : ∀ x → is .snd .inv (is .fst (inr x)) ≡ inr x
elim = elim! λ _ → refl elim
Coequalisers🔗
Given two functions we can compute such that is equivalent to the coequaliser of and We start by expressing the coequaliser as the quotient of by the congruence generated by the relation so that we can apply the result above. Since this relation is clearly decidable by the omniscience of all that remains is to show that the closure of a decidable relation on a finite set is decidable.
instance
Closure-Fin-Dec: ∀ {n ℓ} {R : Fin n → Fin n → Type ℓ}
→ ⦃ ∀ {x y} → Dec (R x y) ⦄
→ ∀ {x y} → Dec (Closure R x y)
This amounts to writing a (verified!) pathfinding algorithm: given we need to decide whether there is a path between and in the undirected graph whose edges are given by
We proceed by induction on the base case is trivial, so we are left with the inductive case The simplest1 way forward is to find a decidable congruence that is equivalent to the closure
We start by defining the restriction of along the successor map written as well as the symmetric closure of written
{suc n} {ℓ} {R} {x} {y} = R*-dec where
Closure-Fin-Dec open Congruence
module R = Congruence (Closure-congruence R)
: Fin n → Fin n → Type _
R₁ = R (fsuc x) (fsuc y)
R₁ x y module R₁ = Congruence (Closure-congruence R₁)
: ∀ {x y} → Closure R₁ x y → Closure R (fsuc x) (fsuc y)
R₁→R = Closure-rec-congruence R₁
R₁→R (Congruence-pullback fsuc (Closure-congruence R)) inc
: Fin (suc n) → Fin (suc n) → Type _
Rˢ = R x y ⊎ R y x
Rˢ x y
: ∀ {x y} → Rˢ x y → Closure R x y
Rˢ→R = [ inc , R.symᶜ ∘ inc ] Rˢ→R
We build by cases. is trivial, since the closure is reflexive.
: {i j : Fin (suc n)} → Fin-view i → Fin-view j → Type ℓ
D' = Lift _ ⊤ D' zero zero
For we use the omniscience of to search for an such that and Here we rely on the closure of being decidable by the induction hypothesis. The case is symmetric.
(suc y) = Σ[ x ∈ Fin n ] Rˢ 0 (fsuc x) × Closure R₁ x y
D' zero (suc x) zero = Σ[ y ∈ Fin n ] Closure R₁ x y × Rˢ (fsuc y) 0 D'
Finally, in order to decide whether and are related by we have two possibilities: either there is a path from to in which we can find using the induction hypothesis, or there are are paths from to and from to in which we can find using the previous two cases.
(suc x) (suc y) = Closure R₁ x y ⊎ D' (suc x) zero × D' zero (suc y) D'
: ∀ i j → Type ℓ
D = D' (fin-view i) (fin-view j) D i j
Proving that (the propositional truncation of)
is a decidable congruence is tedious but not difficult.
: Congruence (Fin (suc n)) _
D-cong instance D-Dec : ∀ {x y} → Dec (D x y)
: Congruence (Fin (suc n)) _
D-cong instance D-Dec : ∀ {x y} → Dec (D x y)
: ∀ x → D x x
D-refl with fin-view i
D-refl i ... | zero = _
... | suc x = inl R₁.reflᶜ
: ∀ x y z → D x y → D y z → D x z
D-trans with fin-view i | fin-view j | fin-view k | p | q
D-trans i j k p q ... | zero | zero | z | _ | d = d
... | zero | suc y | zero | _ | _ = _
... | zero | suc y | suc z | y' , ry , cy | inl c = y' , ry , cy R₁.∙ᶜ c
... | zero | suc y | suc z | _ | inr (_ , dz) = dz
... | suc x | zero | zero | d | _ = d
... | suc x | zero | suc z | dx | dy = inr (dx , dy)
... | suc x | suc y | zero | inl c | y' , cy , ry = y' , c R₁.∙ᶜ cy , ry
... | suc x | suc y | zero | inr (dx , _) | _ = dx
... | suc x | suc y | suc z | inl c | inl d = inl (c R₁.∙ᶜ d)
... | suc x | suc y | suc z | inl c | inr ((y' , cy , ry) , dz) =
((y' , c R₁.∙ᶜ cy , ry) , dz)
inr ... | suc x | suc y | suc z | inr (dx , (y' , ry , cy)) | inl c =
(dx , y' , ry , cy R₁.∙ᶜ c)
inr ... | suc x | suc y | suc z | inr (dx , dy) | inr (dy' , dz) =
(dx , dz)
inr
: ∀ {i j} (x : Fin-view i) (y : Fin-view j) → D' x y → D' y x
D-sym _ = _
D-sym zero zero (suc y) (y' , r , c) = y' , R₁.symᶜ c , ⊎-comm .fst r
D-sym zero (suc x) zero (x' , c , r) = x' , ⊎-comm .fst r , R₁.symᶜ c
D-sym (suc x) (suc y) (inl r) = inl (R₁.symᶜ r)
D-sym (suc x) (suc y) (inr (dx , dy)) =
D-sym (D-sym zero (suc y) dy , D-sym (suc x) zero dx)
inr
._∼_ x y = ∥ D x y ∥
D-cong .has-is-prop _ _ = hlevel 1
D-cong .reflᶜ {x} = inc (D-refl x)
D-cong ._∙ᶜ_ {x} {y} {z} = ∥-∥-map₂ (D-trans x y z)
D-cong .symᶜ {x} {y} = map (D-sym (fin-view x) (fin-view y))
D-cong
{-# INCOHERENT D-Dec #-}
{i} {j} with fin-view i | fin-view j
D-Dec ... | zero | zero = auto
... | zero | suc y = auto
... | suc x | zero = auto
... | suc x | suc y = auto
To complete the proof, we show that is indeed equivalent to it suffices to show that lies between and
: ∀ {x y} → R x y → D x y
R→D {i} {j} r with fin-view i | fin-view j
R→D ... | zero | zero = _
... | zero | suc y = y , inl r , R₁.reflᶜ
... | suc x | zero = x , R₁.reflᶜ , inl r
... | suc x | suc y = inl (inc r)
: ∀ {x y i j} → D' {x} {y} i j → Closure R x y
D→R* {i = zero} {j = zero} _ = R.reflᶜ
D→R* {i = zero} {j = suc y} (y' , r , c) = Rˢ→R r R.∙ᶜ R₁→R c
D→R* {i = suc x} {j = zero} (x' , c , r) = R₁→R c R.∙ᶜ Rˢ→R r
D→R* {i = suc x} {j = suc y} (inl r) = R₁→R r
D→R* {i = suc x} {j = suc y} (inr (dx , dy)) =
D→R* {i = suc x} {j = zero} dx R.∙ᶜ D→R* {i = zero} {suc y} dy
D→R*
: ∀ {x y} → Closure R x y → ∥ D x y ∥
R*→D = Closure-rec-congruence R D-cong (inc ∘ R→D)
R*→D
: Dec (Closure R x y)
R*-dec = invmap (rec! D→R*) R*→D (holds? ∥ D x y ∥) R*-dec
We can finally assemble the pieces together: given the coequaliser of and is equivalent to the quotient of by the decidable relation induced by and and hence by its congruence closure But we know that quotients of finite sets by decidable congruences are finite, and we just proved that the closure of a decidable relation on a finite set is decidable, so we’re done.
Finite-coequaliser: ∀ {n m} (f g : Fin m → Fin n)
→ Σ Nat λ q → Fin q ≃ Coeq f g
{n} f g
Finite-coequaliser = n/R .fst
.snd
, n/R
∙e Closure-quotient R e⁻¹
∙e Coeq≃quotient f g e⁻¹where
= span→R f g
R
: Σ Nat λ q → Fin q ≃ Fin n / Closure R
n/R = Finite-quotient (Closure-congruence R) n/R
In terms of ease of implementation; the complexity of the resulting algorithm is catastrophic.↩︎